Increasing the export potential of raisins (dried grapes) in Uzbekistan by implementing an AHP approach to developing an export strategy - CHITOSE, Atsushi; KUSADOKORO, Motoi; KUVONDIKOV, Dilshod; KAWABATA, Yoshiko (Journal of Arid Land Studies, 2022)
Agriculture plays an important role in Uzbekistan’s economic development. Most of the grapes grown in Uzbekistan are exported as table grapes or raisins, and production of raisins has gradually increased to the point where they are now one of Uzbekistan’s main agricultural exports. Even though Uzbekistan is now one of the world’s top exporters of raisins by volume, its average export price for raisins has remained very low compared with average global prices. Obtaining average global prices for their product would provide better opportunities for agribusiness participants, and in particular would indirectly increase the incomes of small farmers. Therefore, the aim of this study was to develop a sustainable export strategy for agribusinesses in Uzbekistan by identifying the factors responsible for the low prices obtained for exported raisins. Because the export strategy is subject to multi-criteria decision-making, the analytic hierarchy process model was used. All of the factors influencing the final price of raisins were grouped into six categories and the five main commercial raisin varieties were chosen as alternatives. The results showed that the most important factors in determining prices were the quality of the product, the availability of a quality control laboratory, processing facilities and equipment, and certification, while the best variety was the golden raisin. Focusing on these factors would increase export prices by more than 50 percent.